Multimodal surgical decision-making for chest wall sarcomas: a clinical practice review - Cassidy, Devon; Bell, Raheem; Meldrum, Danika E.; Ekeke, Chigozirim N. (Video-Assisted Thoracic Surgery, 2026)
Chest wall sarcomas are rare and biologically diverse tumors that pose unique diagnostic and therapeutic challenges. These malignancies originate from both bone and soft tissue and encompass a wide range of histologic subtypes. Clinical symptoms include enlarging palpable masses and pain, although many lesions present as incidental findings on imaging. Accurate diagnosis relies on comprehensive imaging [computed tomography (CT) and/or magnetic resonance imaging (MRI)] and biopsy for histologic confirmation. Multidisciplinary evaluation is essential to coordinate oncologic and reconstructive planning. Because of the rarity, histologic heterogeneity, and complexity of surgical and reconstructive decision-making, management strategies for chest wall sarcoma are largely derived from retrospective studies, small case series, and institutional experience, while contemporary multidisciplinary guidance remains limited. Surgical resection with negative margins remains the cornerstone of curative therapy. Traditional open approaches remain standard for extensive disease, but minimally invasive techniques such as video-assisted thoracoscopic surgery (VATS) and robotic approaches are increasingly utilized in select patients to reduce surgical morbidity. The extent of resection depends on the structures involved, and surgical strategies are selected to preserve respiratory mechanics and structural integrity. Complex reconstructions may employ prosthetic and biologic materials along with regional or free soft-tissue flaps based on defect size and location. Emerging innovations in imaging, three-dimensional (3D) planning, custom prostheses, and biologic scaffolds are shaping future reconstructive strategies. Despite aggressive multimodal therapy, local recurrence remains a significant concern and highlights the need for vigilant surveillance. This clinical practice review summarizes current evidence and expert perspectives on diagnosis, surgical management, reconstruction, and multimodal therapy for chest wall sarcoma. We present a practical multidisciplinary surgical decision-making flowchart to guide evaluation, treatment sequencing, resection, and reconstruction. Continued research, including multi-center analyses and trials of novel systemic therapies, is necessary to refine surgical decision-making and improve outcomes for patients with chest wall sarcoma.